A chronic rhinosinusitis–derived isolate of Pseudomonas aeruginosa induces acute and pervasive effects on the murine upper airway microbiome and host immune response. Issue 12 (6th September 2016) - Cope, Emily K.; Goldberg, Andrew N.; Pletcher, Steven D.; Lynch, Susan V.
Abstract : Background: Diverse microbial communities colonize healthy sinus mucosa and specific species within these communities are capable of protecting the host from pathogenic infection. However, little is known of the dynamics of upper airway infection and the role of the sinus mucosal microbiome in short‐ and longer‐term outcomes using clinical isolates from patients with chronic rhinosinusitis. Methods: We examine microbiome and immune dynamics after murine sinus infection with Pseudomonas aeruginosa EC1, isolated previously from a chronic rhinosinusitis patient. Microbiota profiling (16S rRNA sequencing), histologic, and immunologic analyses [interferon‐gamma (IFN‐γ) and eotaxin‐1 (CCL11) gene expression] were performed at 1, 7, and 10 days postinfection (D1PI, D7PI, and D10PI) in antimicrobial‐treated and untreated animals. Results: At D1PI, P. aeruginosa EC1 dominated the upper airway microbiome and was associated with a significant increase in sinus mucosa goblet cell hyperplasia, mucin hypersecretion ( p < 0.001), and IFN‐γ expression in antibiotic‐treated and untreated animals, although the magnitude of pathogen enrichment was lower in the latter group. Mucin hypersecretion and IFN‐γ expression subsided by 7D7PI in both groups of mice, coincident with a depletion of the infectious strain. However, other members of the Pseudomonadaceae family remained significantly enriched ( p < 0.05, q < 0.05) in the microbiome at D7PI and D10PI and this perturbation was associated with induction of eotaxin‐1 at these later time‐points. Conclusion: Murine intranasal P. aeruginosa EC1 infection causes a pervasive shift in the sinus microbiome that persists despite histologic resolution and is associated with a reproducible immunologic shift from an initial IFN‐γ response to a temporal induction of eotaxin‐1.